2020
DOI: 10.1186/s12920-020-00740-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analyses of gene expression profile reveal potential crucial roles of mitotic cell cycle and microtubule cytoskeleton in pulmonary artery hypertension

Abstract: Background: Pulmonary arterial hypertension (PAH) is a life-threatening condition. The aim of this study was to explore potential crucial genes and pathways associated with PAH based on integrative analyses of gene expression and to shed light on the identification of biomarker for PAH. Methods: Gene expression profile of pulmonary tissues from 27 PAH patients and 22 normal controls were downloaded from public database (GSE53408 and GSE113439). After the identification of differentially expressed genes (DEGs),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…Downregulated expression of SMC1A, SMC3, and SMC4 could induce growth suppression in lung cancer cells via G1/S cell cycle phase arrest and the apoptosis pathway (Zhang et al, 2013). Another PAH integrative analysis revealed that SMC2 and SMC4 were high hubs and verified their increased expression in PAH patients compared to control patients (Luo et al, 2020). The SMCs family plays key roles in the mitotic cell division machinery (Dávalos et al, 2012), indicating that SMCs might be regulators of cell proliferation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Downregulated expression of SMC1A, SMC3, and SMC4 could induce growth suppression in lung cancer cells via G1/S cell cycle phase arrest and the apoptosis pathway (Zhang et al, 2013). Another PAH integrative analysis revealed that SMC2 and SMC4 were high hubs and verified their increased expression in PAH patients compared to control patients (Luo et al, 2020). The SMCs family plays key roles in the mitotic cell division machinery (Dávalos et al, 2012), indicating that SMCs might be regulators of cell proliferation.…”
Section: Discussionmentioning
confidence: 91%
“…Then, a machine learning-based microarray analysis showed that low-expression genes could also be extremely informative at predicting and distinguishing among different forms of PAH (Cui et al, 2019). Recently, a transcriptomic analysis of PASMCs revealed that genes related to cell proliferation and mitosis are increased in PAH (Luo et al, 2020). However, to date, most studies have been focused on PAHs associated with single disease (Desai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although the previous study yielded some promising biomarkers, we are still skeptical about whether changes in PBMCs at the transcriptomic level can genuinely signal the development of PAH in the lungs. Moreover, some studies have already examined the data sets in this study; however, compared to their conclusion based on differential expression analysis, WGCNA focuses on the interaction between genes in the systemic level and minimizes the loss of information by using soft thresholding (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…It has been successfully applied in some fields, such as breast cancer (9,10). Similarly, the high-throughput strategies also have been applied in the field of PAH (11,12). However, the selection gene features based on differential expression between 2 groups neglects the potential relationships between each gene.…”
Section: Introductionmentioning
confidence: 99%
“…A core subunit of condensin complexes Enriched in facilitating mitotic cell cycle process in PAH (Luo et al, 2020).…”
Section: Smc4mentioning
confidence: 99%